Evaluation of the performance of native chicken and estimation of heritability for body weight (Journal of Bangladesh Academy of Sciences, 2013)
The study was conducted to compare the performance of chickens of non-descript desi (ND), hilly (H) and naked neck (NN) genotypes. Data were analyzed by GLM procedure of SPSS in a CRD. The highest hatchability was found in third hatch of ND (86.38%). The chick weight was influenced (p < 0.05) by the egg weight. The average initial body weight of day-old chicks differed significantly (p < 0.001) by genotypes. The lowest and highest mean body weight gain per bird were recorded for ND (329.38 ± 3.32 g) and NN (351.56 ± 5.08 g) genotypes, which indicated that there were an average daily growth rate of 5.88 ± 0.05 and 6.27 ± 0.09 g per bird per day at their 8th weeks growth phases, respectively. Calculated heritability for 12th week body weight of ND, H and NN were 0.16±0.39, 0.50±0.05 and 0.73±0.25, respectively and for 16th week body weight of H and ND were 0.72±0.15 and 0.35±0.15, respectively. Naked neck is genetically superior to non-descript Desi and Hilly in terms of productive and reproductive parameters. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15685 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 93-101, 2013